Batch and Reverse Flow Injection Spectrophotometric Determination of Nicotine - Ali, Diyar S.; Ibrahim, Wrea M. (Science Journal of University of Zakho, 2016)
Simple and rapid methods for the determination of nicotine using batch and reverse flow injection spectrophotometric system were developed. Nicotine was extracted from different brand of cigarettes. The methods were based on the reaction between nicotine and excess of sodium hypochlorite (NaClO) to form nicotinic acid followed by reaction of NaClO with methyl orange dye (MO). The absorbance of remaining MO in acidic medium at 505 nm was measured. In the batch method, Beer’s law was obeyed in linear range (0.3 – 15 µg/mL) of nicotine with a detection limit of 0.13 µg/mL and correlation coefficient of 0.999. While in reverse flow injection, the calibration graph was linear under the optimum conditions in the range (0.5 – 23.0 µg/mL) of nicotine with a detection limit of 0.13 µg/mL and correlation coefficient of 0.9991. The accuracy and precision of both methods were checked by calculating relative error (E%) and relative standard deviation (RSD%) respectively. Both methods were applied successfully for the determination of nicotine in multiple brands of cigarette products which collected in Erbil City market. The results were compared with standard HPLC method showing no significance differences between two methods.
Keywords: Reverse flow injection analysis; Nicotine; Spectrophotometric; Cigarette